2020
DOI: 10.1016/j.heliyon.2020.e04852
|View full text |Cite
|
Sign up to set email alerts
|

Schottky barrier inhomogeneities at the interface of different epitaxial layer thicknesses of n-GaAs/Ti/Au/Si: Al0.33Ga0.67As

Abstract: The effects of an epitaxial layer on the rectifying behavior of n -GaAs/Ti/Au/Si:Al 0.33 Ga 0.67 As diodes have been examined through the inhomogeneity model on n + -GaAs substrate with orientation. The electrical properties and conduction mechanism of these materials were understood through theoretical models. The inhomogeneity model was used to electrical behavior of these diodes was explained. The barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 35 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…These changes can be explained by an inhomogeneous barrier. The cause of this inhomogeneity can be attributed to different atomic phases, surface defects or the influence of the interface [29]. When the Co/eosin-y/n-Si/Al and Co/eosin-y/p-Si/Al device barrier height values are compared, the Co/hematoxylin/p-Si device has lower barrier height values for the same temperature.…”
Section: Resultsmentioning
confidence: 99%
“…These changes can be explained by an inhomogeneous barrier. The cause of this inhomogeneity can be attributed to different atomic phases, surface defects or the influence of the interface [29]. When the Co/eosin-y/n-Si/Al and Co/eosin-y/p-Si/Al device barrier height values are compared, the Co/hematoxylin/p-Si device has lower barrier height values for the same temperature.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the different doping methods used, some practical PSCs can be either p-type or n-type PSCs, e.g., zinc oxide (ZnO), while some practical PSCs can only be n-type PSCs, e.g., gallium nitride (GaN). When an n-type PSC and metal are bonded together, a Schottky junction appears inevitably at the interface between these two bonded solids [14,15]. Compared with the physical properties of the bulk material, the Schottky junction often has special physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Özdemir et al [21] demonstrated that the potential barrier with GaAs decreases with the increase of the thickness of the Schottky. The semiconductor thickness also has an effect on the Schottky diode characteristics and performance [22]. Kraya and Kraya studied the effect of the contact size on the formation of the Schottky barrier and found that the bigger the size the more likely a Schottky contact is obtained [23].…”
Section: Introductionmentioning
confidence: 99%